Produksi Program Acara “Berkah Islami” di Kompas TV Jawa Tengah (Produser) - Setiarama .; M.Bayu Widagdo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2020)
Television is a medium that is still widely used to obtain information and entertainment by the public. Because of its ease od acces, all people can enjoy television shows. One program that is still in high demand is the religious program. For that reason, the writer and the team created a religious program that could be an alternative choice for the community, namely “Berkah Islami”. Tge producer is in charge of determining the theme, selecting the production team and marketing team, arranging the production schedule, finding sponsors, marketing the program to the audience, and contacting various stockholder during the production process. The Berkah Islami program airs on Kompas TV Jawa Tengah every Sunday at 05.00 AM. Aired for 30 minutes, Berkah Islami discusses about the manners and dunnah that is done everyday. First aired from 1 September 2019 to 24 November 2019.